2023
DOI: 10.1021/acs.macromol.2c02578
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Near-Infrared Emission of π-Conjugated Polymers Consisting of Boron Complexes with Vertically Projected Steric Substituents

Abstract: The development of solid-state near-infrared (NIR)-emissive π-conjugated polymers (CPs) has been still difficult due to lack of valid guidelines for avoiding aggregation-caused quenching. To obtain solid-state emission, we designed new strong electron acceptors by employing boron-fused azobenzene complexes with vertically projected bulky substituents at boron, which can prevent the π-surface from intermolecular interactions. Herein, we demonstrate donor–acceptor-type CPs with NIR emission properties. In summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 78 publications
1
14
1
Order By: Relevance
“…Both polymers showed good solubility in moderately polar organic solvents such as THF, chloroform, and dichloromethane, while they were slightly soluble in nonpolar solvents such as toluene probably due to strong π–π interactions of pyrene moieties. This property was different from previously reported similar polymers with bulky substituents which also showed good solubility in toluene . The chemical structures of all new compounds in this study were confirmed by 1 H, 13 C­{ 1 H}, 11 B NMR spectroscopies, high-resolution mass spectrometry, and elemental analyses (see the Supporting Information).…”
Section: Resultscontrasting
confidence: 91%
See 4 more Smart Citations
“…Both polymers showed good solubility in moderately polar organic solvents such as THF, chloroform, and dichloromethane, while they were slightly soluble in nonpolar solvents such as toluene probably due to strong π–π interactions of pyrene moieties. This property was different from previously reported similar polymers with bulky substituents which also showed good solubility in toluene . The chemical structures of all new compounds in this study were confirmed by 1 H, 13 C­{ 1 H}, 11 B NMR spectroscopies, high-resolution mass spectrometry, and elemental analyses (see the Supporting Information).…”
Section: Resultscontrasting
confidence: 91%
“…This property was different from previously reported similar polymers with bulky substituents which also showed good solubility in toluene. 38 The chemical structures of all new compounds in this study were confirmed by 1 H, 13 C{ 1 H}, 11 B NMR spectroscopies, high-resolution mass spectrometry, and elemental analyses (see the Supporting Information). In addition, we clarified the single-crystal structure of 1-py-Br whose crystal with sufficient size for the analysis was obtained by slow evaporation from acetonitrile solution (Figure S1 and Table S1).…”
Section: ■ Introductionmentioning
confidence: 58%
See 3 more Smart Citations